2020
DOI: 10.13152/ijrvet.7.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Students’ experiences with different learning pathways to higher professional bachelor programmes

Abstract: Context: In the Dutch educational system, different learning pathways to higher professional bachelor (or HBO) programmes have been created: the regular VET route, the general secondary education route, and continuing learning pathways (such as the Green Lyceum or GL) that combine characteristics of these two traditional routes and that are specifically designed for students who combine a relatively high cognitive level with an affinity for practical, vocation-oriented assignments. Approach: The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…From this perspective, SCE should be seen as part of lifelong learning, as a human right and a pathway to employment, health and political participation that must be accessible to all people throughout their lives (United Nations Entity for Gender Equality and the Empowerment of Women [UN WOMEN], 2021a). Several research studies have shown that many students who had dropped out of higher education have the academic potential to successfully complete their education if they are offered appropriate educational alternatives (e.g., Biemans et al, 2020;Franklin et al, 2007;Franklin & Streeter, 1995;Kiprianos & Mpourgos, 2022;Martins et al, 2020).…”
Section: Second Chance In Vocational Education and Trainingmentioning
confidence: 99%
“…From this perspective, SCE should be seen as part of lifelong learning, as a human right and a pathway to employment, health and political participation that must be accessible to all people throughout their lives (United Nations Entity for Gender Equality and the Empowerment of Women [UN WOMEN], 2021a). Several research studies have shown that many students who had dropped out of higher education have the academic potential to successfully complete their education if they are offered appropriate educational alternatives (e.g., Biemans et al, 2020;Franklin et al, 2007;Franklin & Streeter, 1995;Kiprianos & Mpourgos, 2022;Martins et al, 2020).…”
Section: Second Chance In Vocational Education and Trainingmentioning
confidence: 99%
“…Traditionally, students' transitions from one educational level to the next have been characterised by high student drop-out rates with high personal and societal costs as a consequence (Aarkrog et al, 2018;Social and Cultural Planning Agency, 2016;Van den Berg, 2013). A crucial underlying cause for transition problems in VET is the absence of curriculum continuity and integration of successive educational levels (Biemans et al, 2020a). In other words, because VET curricula at successive educational levels are not truly aligned and integrated, many students face difficulties during their transitions between VET levels, with high drop-out rates as a result (see also Catterall et al, 2014;Harris & Rainey, 2012).…”
mentioning
confidence: 99%
“…But what kinds of changes and adaptations in VET curriculum design should be made to achieve these goals and to promote students' acquisition of VET diplomas and transition to Learning Pathways in Dutch VET Compared successive VET levels? Up until now, the international literature on VET curriculum design has not provided clear answers yet (see also Aarkrog et al, 2018;Biemans et al, 2020a). To address these questions, we introduce the concept of continuing learning pathways and describe two of these VET tracks central to this study.…”
mentioning
confidence: 99%
See 2 more Smart Citations